Sjögren's disease and systemic lupus erythematosus overlap: immunological insights and therapeutic implications - Fulvio, Giovanni; La Rocca, Gaetano; Tani, Chiara; Mosca, Marta; Baldini, Chiara (Frontiers in Lupus, 2025)
Sjögren's disease (SjD) and systemic lupus erythematosus (SLE) are distinct autoimmune disorders and their clinical overlap presents a unique immunological entity with specific challenges. While the clinical manifestations of the SjD-SLE overlap have been extensively characterised, its underlying pathogenetic mechanisms remain less understood. This review underscores the immunological features of the overlap, highlighting the roles of genetic predisposition, interferon pathway activation and B-cell dysregulation. Key genetic factors, particularly those associated with HLA and cytokine signaling, underpin disease susceptibility by promoting aberrant immune responses. The consequent and persistent interferon pathway activation drives chronic inflammation and establishes a feedback loop with autoantibody production. Furthermore, Extrafollicular B-cell responses are central to generating hallmark autoantibodies, such as anti-dsDNA and rheumatoid factor, which are frequent in the overlap. Finally, the continuous activation of interferons and B-cells not only increase disease activity but also contributes to lymphoproliferative complications. Despite progress in elucidating these mechanisms, patients with SjD-SLE overlap remain underrepresented in clinical trials, limiting therapeutic advancements. Emerging strategies, including interferon receptor inhibitors, BAFF-blocking antibodies, and advanced B-cell depletion therapies, may offer promising options to hit the distinct immunological abnormalities of these patients.